Pre-Existing Diabetes Limits Survival Rate After Immune Checkpoint Inhibitor Treatment for Advanced Lung Cancer: A Retrospective Study in Japan [Corrigendum] - Hisanaga K (Dove Medical Press, 2021)
Hisanaga K, Uchino H, Kakisu N, et al. Diabetes Metab Syndr Obes. 2021;14:773—781. Page 775, left column, third paragraph, line 4, the text “(p<0.5)” should read “(p<0.05)”. Page 775, left column, second line from the bottom, the text “11.3±20.8” should read “113.0±20.8”. Page 776, Table 1, Plasma glucose (mg/dl) row, Unmatched, Non-DM (n=64) column, the value “11.3±20.8” should read “113.0±20.8”. The authors apologize for these errors. Read the original article